Zr-B-C coating with high hardness and high toughness and preparation method thereof
The Zr-BC coating addresses the toughness limitations of ZrB2 by doping with C, achieving high hardness and toughness while maintaining thermal stability and wear resistance, suitable for industrial applications.
Patent Information
- Application Number
- CN202410850936.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-01-03
AI Technical Summary
Existing ZrB2 coatings suffer from poor toughness due to anisotropic columnar crystal structure and reactivity with oxygen, limiting their use in oxidizing environments and reducing their mechanical performance.
A Zr-BC coating is prepared by doping ZrB2 with a C element using high-power pulsed magnetron sputtering and pulsed DC magnetron sputtering composite coating technology, optimizing C content and process parameters to enhance hardness and toughness.
The Zr-BC coating achieves high hardness and toughness, maintaining thermal stability and wear resistance, with a friction coefficient as low as 0.869 and wear rate of 2.3×10^-7 mm^3/(mm·N), suitable for processing difficult-to-cut materials and extending tool life.
Smart Images

Figure CN119243096A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to a Zr-BC coating having high hardness and high toughness and a preparation method thereof. Background Art
[0002] Hard coating refers to a coating of a few nanometers to tens of nanometers applied to the surface of a workpiece or cutting tool, which can significantly improve the wear resistance, corrosion resistance and high temperature resistance of the material surface. The material is mainly composed of compounds composed of transition metals and non-metals (B, C, N, O) connected by covalent bonds, metallic bonds, and ionic bonds. With the rapid development of modern industry, mechanical manufacturing technology is developing in the direction of high efficiency, high precision, high reliability and specialization. In order to improve processing efficiency and precision and reduce production costs, people have vigorously carried out research on superhard materials and difficult-to-process materials and developed hard coatings that meet engineering needs. Traditional superhard materials, such as diamond and cubic boron nitride (c-BN), are widely used in cutting tools, wear-resistant coatings, abrasive materials, aerospace, geological exploration and other fields due to their high hardness (HV>40GPa), excellent wear resistance and chemical stability. However, diamond is prone to oxidation reaction when heated to 600℃ in the atmosphere and has poor thermal stability; it easily reacts with iron group elements and cannot process ferrous metal materials; diamond reserves in nature are small, and artificially synthesized diamonds have complex preparation conditions, difficulty in making complex shapes, and high production costs, which seriously limit the scope of diamond use. Therefore, finding new materials to replace diamond has become the focus of researchers in recent years.
[0003] As we all know, boron is an electron-deficient, lightweight non-metallic element. Boron and B can form a variety of covalent bond hybridization forms (sp, sp 2 ,sp 3 ), and can both gain and lose electrons. Doping it with transition metals with high valence electron density can form a variety of chemical bonds, including MM metal bonds, BB covalent bonds, and BM ionic bonds. These structural characteristics determine that transition metal borides have a stable structure and a series of excellent physical and chemical properties, such as high hardness, high melting point, electrical and thermal conductivity, good fracture toughness and wear resistance, and can also be used as hydrogen storage materials. However, due to the limited preparation process and uncertainty of characterization methods, the research on transition metal borides is far less comprehensive and in-depth than that on carbides and nitrides. Therefore, research and exploration of transition metal borides has very important scientific value, which can take the research and application of hard films to a new level.
[0004] The transition metal boride ZrB2 coating is a close-packed hexagonal crystal structure with high thermal conductivity and good thermal shock resistance. At the same time, the ZrB2 coating also has the advantages of high hardness, high melting point, high oxidation resistance, low resistivity, and good electrical conductivity. However, ZrB2 easily reacts with oxygen at high temperatures to form a ZrO2 / B2O3 oxide layer, and single-crystalline ZrB2 cannot be used in an oxidizing environment above 1200°C. In addition, the columnar crystal (001) texture in the coating makes it anisotropic, and its grain boundaries perpendicular to the surface provide a short crack propagation path, which greatly reduces its toughness. The present invention intends to add a new element (C element) to the transition metal boride, and study and explore the preparation process (process parameters) so that the prepared nanocomposite coating has better performance. Summary of the invention
[0005] In order to further improve the toughness of the existing Zr-B coating, the purpose of the present invention is to provide a Zr-BC coating with both high hardness and high toughness and a preparation method thereof. High-power pulsed magnetron sputtering and pulsed DC magnetron sputtering composite coating technology are used to dope the ZrB2 coating with C element to form a Zr-BC coating. Through process design and optimization of the C element content, a Zr-BC coating with both high hardness and high toughness is prepared.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A Zr-BC coating with both high hardness and high toughness, characterized in that: the Zr-BC coating is deposited on a metal (cemented carbide substrate or SUS 304 stainless steel sheet) or a silicon wafer substrate, and in the Zr-BC coating, C is 28.5-41.9at.%, B is 14.7-28.2at.%, Zr is 20.9-39.1at.%, and O is 3.1-6.5at.%.
[0008] In the Zr-BC coating, as the content gradually increases, the content of B, O and Zr elements shows a downward trend, and the C / Zr atomic ratio in the Zr-BC coating is greater than 1.
[0009] The Zr-BC coating includes ZrB2, ZrC, Zr3C2, ZrC 0.7 Crystal phase, among which the ZrB2 crystal phase is mainly composed of hexagonal close-packed (hcp) structure, and the ZrC crystal phase is mainly composed of face-centered cubic (fcc) structure.
[0010] A Zr transition layer is provided between the Zr-BC coating and the substrate.
[0011] The preparation method of the Zr-BC coating with high hardness and high toughness is to deposit the Zr-BC coating on the substrate by using pulsed DC magnetron sputtering technology. When depositing the Zr-BC coating, the ZrB2 target is turned on and the process is carried out in a mixed atmosphere of Ar and C2H2, wherein: the background pressure is 3×10 -3 Pa, the deposition temperature is 370-450℃, the ZrB2 target power is 1.2-1.8kW; the Ar flow rate is 100-120sccm, the C2H2 flow rate is 3-18sccm (preferably 9-15sccm), and the deposition time is 240-280min; different acetylene (C2H2) flow rates are set according to experimental requirements.
[0012] The method for preparing the Zr-BC coating with high hardness and high toughness specifically comprises the following steps:
[0013] (1) Fix the cleaned substrate on the rotating rack in the coating chamber, fix the Zr target at the high power target position, and fix the ZrB2 at the DC target position; evacuate to a vacuum degree of 3.0×10 -3 Pa or above; the purity of the Zr target and the ZrB2 target are both 99.95%.
[0014] (2) The substrate is sequentially subjected to glow discharge cleaning and ion bombardment cleaning; the glow discharge cleaning process is as follows: the furnace chamber is heated to 370-450°C, and the vacuum chamber is evacuated to a vacuum degree of 3×10 -3 Pa or more, then introduce Ar, Ar flow rate 180-220sccm, adjust the working pressure to be stable at 1.5-1.7Pa, pulse bias -780~-800V, bias duty cycle 85-87%, glow cleaning 15-18min; the ion bombardment cleaning process is: after glow discharge cleaning, adjust the Ar flow rate to 180-200sccm, adjust the deposition pressure to be stable at 0.8-0.9Pa, turn on the Zr target (the Zr target is connected to a high-power pulsed magnetron sputtering power supply), Zr target power 1-1.3kW, pulse bias -760~-800V, bias duty cycle 85-87%, deposition 8-10min.
[0015] (3) Deposition of transition layer: The Zr transition layer is deposited by high-power pulsed magnetron sputtering technology, and an Ar target is used to improve the bonding strength between the working layer and the substrate. The process of depositing the transition layer is as follows: after glow discharge cleaning and ion bombardment cleaning, the Ar flow rate is adjusted to 80-100 sccm, the deposition pressure is adjusted to be stable at 0.7-0.8 Pa, and the Zr target is turned on (the Zr target is connected to a high-power pulsed magnetron sputtering power supply), the Zr target power is 1.0-1.2 kW, the pulse bias voltage is -140 to -150 V, the bias duty cycle is 48-50%, and the deposition time is 20-23 min;
[0016] (4) Deposition of Zr-BC coating.
[0017] Furthermore, in step (2), the glow discharge cleaning process is as follows: the temperature in the furnace is heated to 370-450°C, and the vacuum chamber is evacuated to a vacuum degree of 3×10 -3 Pa, then introduce Ar with a flow rate of 180-220sccm, adjust the working pressure to be stable at 1.5-1.7Pa, set the pulse bias to -780~-800V, the bias duty cycle to 85-87%, and glow clean for 15-18min.
[0018] Furthermore, in step (2), the ion bombardment cleaning process is as follows: after glow discharge cleaning, the Ar flow rate is adjusted to 180-200sccm, the working pressure is adjusted to be stable at 0.8-0.9Pa, the Zr target is turned on (the Zr target is connected to a high-power pulsed magnetron sputtering power supply), the Zr target power is set to 1-1.3kW, the pulse bias is -760~-800V, the bias duty cycle is 85-87%, and the bombardment cleaning time is 8-10min.
[0019] Furthermore, in step (3), the process of depositing the Zr transition layer is as follows: after glow discharge cleaning and ion bombardment cleaning, the Ar flow rate is adjusted to 80-100 sccm, the deposition pressure is adjusted to be stable at 0.7-0.8 Pa, the Zr target is turned on (the Zr target is connected to a high-power pulsed magnetron sputtering power supply), the Zr target power is set to 1.0-1.2 kW, the pulse bias is -140 to -150 V, the bias duty cycle is 48-50%, and the deposition time is 20-23 min.
[0020] Furthermore, the purity of the Zr target and the ZrB2 target is 99.95%; when depositing the Zr-BC coating, as the acetylene flow rate increases, the contents of B, O, and Zr elements in the coating show a downward trend, and the C content gradually increases.
[0021] The hardness of the Zr-BC coating is as high as 23 GPa, the friction coefficient of the coating is as low as 0.869, and the wear rate of the coating is as low as 2.3×10 -7 mm 3 / (mm·N).
[0022] The design mechanism of the present invention is as follows:
[0023] The invention adopts pulse magnetron sputtering and pulse DC magnetron sputtering composite coating technology to deposit Zr-BC coating on hard alloy sheet, SUS304 stainless steel and single crystal Si sheet.
[0024] Transition metal borides TMB are widely used in industrial production and aerospace fields due to their excellent properties such as high melting point, ultra-high hardness, and thermodynamic stability. Adding new elements to transition metal borides can prepare nanocomposite films with excellent performance. Since the fracture toughness of ZrB2 film is poor, the present invention adds light element C to the transition metal boride ZrB2 to form a multi-element Zr-BC film, which can not only change the microstructure of the film, but also may produce a variety of new phases, thereby improving the comprehensive performance of binary borides. Furthermore, the present invention further improves the hardness and toughness of the coating without significantly reducing the mechanical properties and tribological properties of the ZrB2 coating by regulating the acetylene flow rate and coordinating other process parameters (target power, bias voltage, pressure, etc.), by designing process conditions and optimizing the C element content, and giving full play to the high hardness, high toughness and low friction coefficient characteristics of the coating.
[0025] The advantages and beneficial effects of the present invention are as follows:
[0026] 1. The Zr-BC coating prepared by the present invention has high wear resistance and obvious wear resistance effect.
[0027] 2. The Zr-BC coating of the present invention maintains the original high hardness, high melting point and high thermal stability characteristics of the ZrB2 coating. By adding the C element, the toughness of the coating is increased, and a Zr-BC coating with high hardness and high toughness is prepared.
[0028] 3. The Zr-BC coating of the present invention has broad application prospects and is suitable for various difficult-to-process materials, greatly improving cutting efficiency and tool service life.
[0029] 4. The Zr-BC coating of the present invention has excellent mechanical and tribological properties, and the coated tool can be suitable for heavy-load continued processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Elemental compositions of the Zr-BC coating prepared in Example 1 at different acetylene flow rates.
[0031] Figure 2 XRD patterns of the Zr-BC coating prepared in Example 1 at different acetylene flow rates.
[0032] Figure 3 Surface morphology of the Zr-BC coating prepared in Example 1 under different acetylene flow rates; wherein: (a) acetylene flow rate 0 sccm; (b) acetylene flow rate 5 sccm; (c) acetylene flow rate 8 sccm; (d) acetylene flow rate 10 sccm; (e) acetylene flow rate 12 sccm; (f) acetylene flow rate 15 sccm.
[0033] Figure 4The cross-sectional morphologies of the Zr-BC coating prepared in Example 1 at different acetylene flow rates; wherein: (a) acetylene flow rate 0 sccm; (b) acetylene flow rate 5 sccm; (c) acetylene flow rate 8 sccm; (d) acetylene flow rate 10 sccm; (e) acetylene flow rate 12 sccm; (f) acetylene flow rate 15 sccm.
[0034] Figure 5 The deposition rate of the Zr-BC coating prepared in Example 1 at different acetylene flow rates.
[0035] Figure 6 The hardness and elastic modulus of the Zr-BC coating at different acetylene flow rates prepared by high-power pulsed magnetron sputtering and pulsed DC magnetron sputtering composite coating technology in Example 1.
[0036] Figure 7 H / E and H of the Zr-BC coating prepared in Example 1 at different acetylene flow rates 3 / E* 2 .
[0037] Figure 8 Critical load of the Zr-BC coating prepared in Example 1 at different acetylene flow rates.
[0038] Fig. 9 The scratch morphology of the Zr-BC coating prepared in Example 1 at different acetylene flow rates.
[0039] Fig.10 The residual tensile stress of the Zr-BC coating prepared in Example 1 under different acetylene flow rates.
[0040] Fig.11 The friction coefficient of the Zr-BC coating prepared in Example 1 at different acetylene flow rates.
[0041] Fig.12 The wear rate of the Zr-BC coating prepared in Example 1 under different acetylene flow rates.
[0042] Fig.13 The wear scar morphology of the Zr-BC coating prepared in Example 1 under different acetylene flow rates; among which: (a) acetylene flow rate 0 sccm; (b) acetylene flow rate 5 sccm; (c) acetylene flow rate 8 sccm; (d) acetylene flow rate 10 sccm; (e) acetylene flow rate 12 sccm; (f) acetylene flow rate 15 sccm. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below by way of examples.
[0044] In the following examples, the purity of the Zr target and the ZrB2 target are both 99.95%.
[0045] Embodiment 1:
[0046] This example is to prepare Zr-BC coatings with different C contents.
[0047] This embodiment deposits Zr-BC coating on single crystal Si wafer (30mm×30mm×0.67mm), cemented carbide wafer (25mm×25mm×3.0mm) and stainless steel wafer (35mm×35mm×1.0mm), using high power pulsed magnetron sputtering and pulsed DC magnetron composite coating technology. The specific operation steps are as follows:
[0048] (1) Substrate pretreatment: After polishing the cemented carbide substrate, place it in an ultrasonic cleaning machine with the pre-prepared single crystal Si wafer and 304 stainless steel sheet, and use acetone and alcohol for ultrasonic cleaning for 20 minutes respectively. After cleaning, blow it dry with high-purity N2 (99.99%). The substrate is fixed on the sample plate. After the vacuum chamber is vented, open the vacuum chamber furnace door, fix the sample plate on the rotating rack in the coating chamber with iron wire, fix the Zr target at the high-power target position, and fix the ZrB2 at the DC target position; adjust the fixed position of the sample plate so that the substrate is facing the target surface to prevent the surface deposition distance from being different during the deposition process, resulting in uneven coating preparation. Check that there is no foreign matter left in the vacuum chamber and close the furnace door.
[0049] (2) Vacuuming: Since the molecular pump cannot work when the pressure in the vacuum chamber is higher than 4.0Pa, vacuuming is divided into two steps. First, vacuuming is started at atmospheric pressure. The vacuum chamber is evacuated using a TRP-90 roughing pump. When the vacuum degree is roughly drawn to 4.0Pa, the mechanical pump and the molecular pump are turned on to accelerate the molecular pump. When the acceleration is completed and the vacuum degree is higher than 4.0Pa, the fine pumping valve is opened to further evacuate the chamber until the pressure in the vacuum chamber reaches 3.0×10 -3 Pa, turn on the heating source to heat the vacuum chamber, set the final temperature to 400°C, the alarm temperature to 450°C, and keep the rotating frame rotating at 40Hz during the heating process to ensure that the substrate is heated evenly. -3 Pa or above.
[0050] (3) Glow discharge cleaning of the vacuum chamber: When the temperature and vacuum degree in the vacuum chamber meet the requirements, introduce 200 sccm of Ar into the vacuum chamber, adjust the pressure in the vacuum chamber to be stable at 1.5 Pa, turn on the intermediate frequency power supply, adjust the high position, adjust the substrate bias voltage to -800 V, and the duty cycle to 87%. During the adjustment, always pay attention to the alarm indication of the intermediate frequency power supply. When the discharge in the vacuum chamber is serious, slowly adjust the substrate bias voltage to avoid damaging the equipment. The glow discharge cleaning lasts for 15 minutes.
[0051] (4) Bombarding and cleaning the target surface: introduce Ar at a flow rate of 200 sccm, adjust the working pressure to be stable at 0.8 Pa, turn on the Zr target, power 1 kW, pulse bias -800 V, bias duty cycle 87%, and bombard and clean for 8 minutes.
[0052] (5) When depositing the transition layer, an Ar flow rate of 100 sccm was introduced, the deposition pressure was adjusted to be stable at 0.8 Pa, the Zr target was turned on, the power was 1.2 kW, the pulse bias was -150 V, the bias duty cycle was 50%, and the deposition was carried out for 20 min.
[0053] (6) Deposit Zr-BC coating by introducing Ar 100 sccm and setting C2H2 to 0 sccm, 5 sccm, 8 sccm, 10 sccm, 12 sccm and 15 sccm respectively. Adjust the deposition pressure to be stable at 1.6 kW, turn on the ZrB2 target fixed on the DC target, pulse bias -150 V, bias duty cycle 50%, and deposit for 240 min.
[0054] The morphology and performance of multiple Zr-BC coating samples with different acetylene flow rates prepared in this example were characterized as follows:
[0055] The phase composition of the coating was analyzed by X-ray diffractometer (XRD). The data was collected by step scanning. The incident X-ray was radiated by Cu target Kα characteristic spectrum (λ=0.154056nm), tube voltage was 40kV, tube current was 40mA, diffraction angle (2θ) scanning range was 20°~80°, scanning step length was 0.02°, and counting time per step was 0.2s. The surface and cross-sectional morphology of the coating were observed by S4800 field emission scanning electron microscope (SEM), and the chemical composition of the coating was analyzed by electron probe (EPMA, Shimadzu, EPMA1600).
[0056] The hardness and elastic modulus of the coating were tested by a nanoindenter (Anton Paar, TTX-NHT-3). To eliminate the influence of the matrix effect on the measurement results, the tip penetration depth was ensured to be no more than 1 / 10 of the coating thickness, and the average value was taken by measuring 15 points. The bonding strength between the coating and the SUS 304 stainless steel substrate was measured by a scratch tester (Anton Paar RST-3). The diameter of the diamond tip was 200 μm, and the parameters were as follows: loading speed 6 mm / min; scratch length 3 mm; set load 100 N, and the experimental data was recorded in real time by a computer.
[0057] The friction coefficient was tested on a friction and wear tester (Anton Paar THT). The friction pair was selected with a 6mm diameter Al2O3 ball (hardness 22±1GPa), a sliding linear velocity of 0.1m / s, a normal load of 4N, a rotation radius of 6mm, and a sliding distance of 100m. The friction test was carried out at room temperature of 22±3℃ and humidity of 30%. Each sample was tested 3 times. The coating wear rate W was calculated using the formula W=V / (F×S) (V is the wear volume, F is the normal load, and S is the sliding distance). In addition, an ultra-depth microscope (VHX-1000C, Keyence) was used to observe the morphology of the coating after wear.
[0058] Figure 1 The composition of each element in the Zr-BC coating deposited under different acetylene flow rates. As can be seen from the figure, with the increase of acetylene flow rate, the content of B, O, and Zr elements in the coating shows a downward trend, and the C content gradually increases. When the acetylene flow rate is 0sccm, there are 6.49at.% O and 13at.% C in the coating. This is mainly due to the reaction of the target material with the impurities remaining in the vacuum chamber during the deposition process. With the continuous increase of acetylene flow rate, the C element in the coating increases from 13at.% to 41.9at.%, which is attributed to the fact that acetylene is introduced into the vacuum chamber as a reaction gas, and the kinetic energy of C atoms continues to increase, which intensifies the collision with the substrate, resulting in a gradual increase in the C content in the coating. The continuous decrease in the content of B, O, and Zr in the coating is due to the fact that the C / Zr ratio in the Zr-BC coating is greater than 1. Combined with the XRD diagram, not only ZrC crystals are generated in the coating, but also amorphous CN or C single substance is formed, which promotes the grain refinement of the coating and makes it difficult for the O element to enter the coating.
[0059] Figure 2 The XRD patterns of Zr-BC coatings deposited under different acetylene flow rates are shown in Figure 1. 0.7 Crystal phase composition, no O content was detected in the coating, indicating that the oxygen element has been removed in the vacuum chamber, and a high-purity Zr-BC coating can be prepared. When the acetylene flow rate is 0sccm, only the hcp-ZrB2 crystal phase can be detected in the coating, and the (001) crystal plane is the preferred orientation of the coating. With the increase of acetylene flow rate, the preferred orientation of the coating changes from the (001) crystal plane to the (200) crystal plane. At 2θ=68.296°, the (200) crystal plane ZrB2 phase diffraction peak can be detected in all coatings, but with the increase of C content, the intensity of the ZrB2 diffraction peak gradually decreases and broadens, indicating that the addition of C element inhibits the growth of ZrB2 crystals and refines the grains to a certain extent. When the acetylene flow rate is 5sccm, the main forms of C are Zr3C2(110), ZrC 0.7(622) crystal plane diffraction peak. When the acetylene flow rate is 15 sccm, a weak ZrC 0.7 (310) crystal plane diffraction peak, no diffraction peaks of C content were detected in other coatings. The C element may exist in the coating in amorphous or simple form to form a composite structure of amorphous encapsulating nanocrystals.
[0060] Figure 3 The surface morphology of the Zr-BC coating deposited under different acetylene flow rates. With the increase of acetylene flow rate, the coating surface gradually tends to be smooth and dense. This shows that the increase of C element greatly promotes grain refinement. When the acetylene flow rate is 5sccm, particles appear on the coating surface and it is disorderly. This is because when the C content is low, the nucleation speed is slow, the grain size is small, and there are more fine particles on the surface. When the acetylene flow rate increases from 8sccm to 15sccm, the deposition rate increases, the grain size increases, and the coating nucleation ability also increases. At the same time, the incident particle energy increases, which promotes the repeated nucleation and recrystallization of the deposited particles, promotes grain refinement, improves the diffusion ability of the deposited particles on the coating surface, and promotes the uniformity and density of the coating.
[0061] Figure 4 The cross-sectional morphology of the Zr-BC coating deposited under different acetylene flow rates. As can be seen from the figure, with the increase of acetylene flow rate, the C content also increases, the columnar crystal shape of the film gradually disappears, and a dense fibrous structure appears. This is attributed to the fact that with the increase of C content, the amorphous phase inside the coating gradually increases, and the amorphous phase wraps the crystalline phase to inhibit the growth of the grains, and the columnar crystal structure cannot be formed. When the acetylene flow rate is 8sccm, the cross-section of the film has an obvious columnar shape, and the grains are coarse and large, and the structure is loose. However, when the acetylene flow rate is 10sccm, the columnar shape of the film has gradually blurred and turned into an indefinite shape. When the acetylene flow rate is 15sccm, the film structure has become needle-shaped, and is closely arranged perpendicular to the substrate surface, promoting the preferential growth of the grains.
[0062] Figure 5 The deposition rate of Zr-BC coating deposited under different acetylene flow rates. As can be seen from the figure, with the increase of acetylene flow rate, the deposition rate of Zr-BC coating first decreases and then increases. When the acetylene flow rate is 8sccm, the deposition rate of the coating reaches the lowest, which is 7.7nm / min. Figure 4 (c) As the acetylene flow rate increases, the sputtering rate of the reaction gas is lower, and the number of deposits on the substrate surface is small in the same time, and the bonding force is poor, so the deposition rate will decrease accordingly. When the acetylene flow rate is 15sccm, the number of ions in the chamber increases, and the collisions between particles also increase, which increases the number of deposited C atoms and the deposition rate.
[0063] Figure 6The hardness (HIT) and elastic modulus (EIT) of Zr-BC coatings deposited under different acetylene flow rates. As shown in the figure, with the increase of acetylene flow rate, the hardness shows a trend of first decreasing, then increasing, and then decreasing. When the acetylene flow rate is 10sccm, the hardness of the coating reaches the highest value, about 23GPa. This is mainly because when a small amount of acetylene is introduced, the number of C ions in the cavity is small, the hard phase of the coating is reduced, and the hardness of the coating is reduced. The Hall-Petch strengthening theory points out that the strength of the coating depends on the size of the grains. The smaller the grains, the higher the hardness of the coating. As the acetylene flow rate increases from 5sccm to 10sccm, the hardness of the coating increases from about 18.8GPa to 23GPa, indicating that with the increase of C content, the ions in the cavity obtain more energy, making the coating structure dense and the hardness increased. When the acetylene flow rate increases further, the hardness of the coating decreases, indicating that the energy is too large and the bombardment is too strong, making the coating surface uneven, resulting in a decrease in hardness. The elastic modulus of the coating shows a trend of gradually decreasing with the increase of acetylene flow rate.
[0064] Figure 7 H / E and H of Zr-BC coatings deposited under different acetylene flow rates 3 / E* 2 As can be seen from the figure, the characteristic value of the coating shows a trend of first increasing, then decreasing, and then increasing again. It can be seen from the figure that the maximum is reached when the acetylene flow rate is 10sccm, indicating that the toughness and wear resistance of the coating have reached the optimal level at this time. The study found that the smaller the elastic modulus, the more the applied load can be distributed in a wider coating area, which improves the toughness of the coating under high hardness conditions.
[0065] Figure 8 is the critical load of the Zr-BC coating deposited under different acetylene flow rates. As can be seen from the figure, with the increase of acetylene flow rate, the critical load of the coating shows a trend of first decreasing, then increasing, and then decreasing. When the acetylene flow rate is 12sccm, the critical load of the coating is 51N at most. The reason is that the particles have obtained huge energy, which makes them have strong adhesion ability, increased kinetic energy, enhanced adsorption ability, and increased bonding force. When the acetylene flow rate varies from 0sccm to 10sccm, the critical load of the coating gradually decreases slightly. The reason is that due to the doping of C element, part of the B element is replaced, the parameter change between the crystals causes lattice distortion, the internal stress of the coating increases, and the film / substrate bonding strength decreases. When the acetylene flow rate is 15sccm, the critical load of the coating decreases rapidly. By observing the scratch morphology, it is found that obvious cracks have appeared at the starting point of the scratch, indicating that the increase in C content has intensified the bombardment speed of the particles on the substrate, causing the temperature of the substrate to increase, and the addition of thermal stress has weakened the film / substrate bonding to a certain extent. Fig. 9 Scratch morphology of Zr-BC coating deposited under different C2H2 flow rates.
[0066] Fig.10is the residual tensile stress of Zr-BC coating deposited under different acetylene flow rates. As can be seen from the figure, when the acetylene flow rate is 0sccm, the residual tensile stress of the coating is the largest, which is 0.307GPa. After the acetylene is introduced, it shows a trend of increasing first, then decreasing, and then increasing again. The residual tensile stress in the coating generally comes from the bombardment between particles, the lattice distortion caused by doping atoms, and the phase change in the coating preparation. During the deposition process of the coating, C atoms collide with the target material, generate high energy and leave the target surface. Since the radius of C atoms is smaller than that of Ar atoms, the mean free path of Ar atoms is lower than that of C atoms. The number of collisions between the reflected C atoms and neutral atoms and working gases is reduced, and the energy loss is small when they finally reach the substrate. Due to the bombardment between high-energy particles, some defects in the coating are merged, and the increase of C atoms in the coating causes lattice distortion, resulting in compressive stress in the coating. When the C2H2 partial pressure increases, the increase in C atoms significantly increases the atomic pinning effect, thereby increasing the compressive stress in the coating. When the acetylene flow rate is greater than 10 sccm, the compressive stress in the coating decreases, mainly because more soft phase amorphous aC is generated in the coating, and the soft phase can release part of the stress in the film.
[0067] Fig.11 and Fig.12 The friction coefficient and wear rate of the Zr-BC coating deposited under different acetylene flow rates. As can be seen from the figure, with the increase of acetylene flow rate, the friction coefficient and wear rate of the coating show a gradually decreasing trend. The friction coefficient and wear rate when no acetylene is introduced are significantly higher than those when acetylene is introduced, indicating that the addition of C element makes the coating denser and the coating structure more stable. When the acetylene flow rate is 10sccm, the friction coefficient and wear rate reach the minimum value, which are 0.869 and 2.3×10 -7 mm 3 / (mm·N). The reasons are as follows: 1. By observing the mechanical properties, it is found that the hardness of the coating is the highest when the acetylene flow rate is 10sccm. The higher the hardness of the coating, the better the wear resistance; 2. The coating has a higher H / E and H at this time. 3 / E* 2 The value indicates that the coating has good anti-friction performance; 3. The coating also has good residual tensile stress at this time, which can alleviate the cracks generated during wear to a certain extent; 4. By observing the microscopic morphology, the surface roughness of the coating is also relatively low at this time, which can increase the friction and wear performance of the coating; 5. With the increase of C content, amorphous C or elemental C appears in the coating, which has a lubricating effect during the wear process. When the acetylene flow rate is 12sccm, the friction coefficient and wear rate of the coating increase slightly, which is due to the hardness, H / E, and H 3 / E* 2When the acetylene flow rate is 15 sccm, the friction coefficient of the coating drops sharply to only 0.645, and the wear rate is as low as 1.9×10 -7 mm 3 / (mm·N), at this time, the C element in the coating is in the form of sp 2 The presence of bonds can effectively reduce the shear stress of the friction interface and thus reduce the friction coefficient. Although the hardness of the film is low at this time, more amorphous C has been generated in the film, which enhances the self-lubricating ability of the film and has appropriate compressive stress.
[0068] Fig.13 The wear scar morphology of Zr-BC coating under different acetylene flow rates. As can be seen from the figure, when the acetylene flow rate is 10sccm, the wear scar width is the narrowest, the edge is not obvious, and no peeling and cracking occurs during the friction process, indicating that the wear resistance of the film is significantly improved. At this time, the toughness of the film is the best, which means that it is easier to slip under shear force, thereby avoiding the occurrence of plowing wear. When the acetylene flow rate is 5sccm, the wear scar of the film is the widest. At this time, the H / E and H 3 / E* 2 The minimum means that the elastic deformation resistance is low, and the external load cannot be effectively released in a larger area, which directly leads to an increase in the friction cross section. At the same time, the edge of the wear scar peels off in a serrated manner. During the friction process, the peeled chips cannot be removed in time and are pressed into the wear scar surface, causing new abrasive wear on the film. When the acetylene flow rate reaches 12sccm and 15sccm, the wear scar width increases, the film wear is aggravated, and when the acetylene flow rate is 15sccm, a large amount of black chips are distributed on both sides of the wear scar of the film, and some of the chips are compacted on the wear scar surface. This part of the compacted chips acts as a lubricating film to reduce wear.
[0069] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A Zr-BC coating with high hardness and high toughness, characterized in that: The Zr-BC coating is deposited on a metal or silicon wafer substrate. In the Zr-BC coating, C is 28.5-41.9 at.%, B is 14.7-28.2 at.%, Zr is 20.9-39.1 at.%, and O is 3.1-6.5 at.%.
2. The Zr-BC coating with high hardness and high toughness according to claim 1, characterized in that: In the Zr-BC coating, as the content gradually increases, the content of B, O and Zr elements shows a downward trend, and the C / Zr atomic ratio in the Zr-BC coating is greater than 1.
3. The Zr-BC coating with high hardness and high toughness according to claim 1, characterized in that: The Zr-BC coating includes ZrB2, ZrC, Zr3C2, ZrC 0.7 Crystal phase, among which the ZrB2 crystal phase is mainly composed of hexagonal close-packed (hcp) structure, and the ZrC crystal phase is mainly composed of face-centered cubic (fcc) structure.
4. The Zr-BC coating with high hardness and high toughness according to claim 1, characterized in that: A Zr transition layer is provided between the Zr-BC coating and the substrate.
5. The method for preparing a Zr-BC coating having high hardness and high toughness according to any one of claims 1 to 4, characterized in that: The method is to deposit Zr-BC coating on the substrate by pulsed DC magnetron sputtering technology. When depositing Zr-BC coating, ZrB2 target is turned on and the process is carried out in a mixed atmosphere of Ar and C2H2, wherein: the background pressure is 3×10 -3 Below Pa, the deposition temperature is 370-450℃, the ZrB2 target power is 1.2-1.8kW; the Ar flow rate is 100-120sccm, the C2H2 flow rate is 3-18sccm, and the deposition time is 240-280min.
6. The method for preparing a Zr-BC coating having both high hardness and high toughness according to claim 5, characterized in that: The method specifically comprises the following steps: (1) Wash and dry the substrate, fix it on the sample plate, and hang it on the rotating rack in the coating room. Pump the vacuum degree in the coating room to 3.0×10 -3 Pa or above; (2) performing glow discharge cleaning and ion bombardment cleaning on the substrate in sequence; (3) Depositing the Zr transition layer by high-power pulsed magnetron sputtering technology, using a Zr target, with a deposition time of 18-20 min to improve the bonding strength between the working layer and the substrate; (4) Deposition of Zr-BC coating.
7. The method for preparing a Zr-BC coating having both high hardness and high toughness according to claim 6, characterized in that: In step (2), the glow discharge cleaning process is as follows: the temperature in the furnace is heated to 370-450°C, and the vacuum chamber is evacuated to a vacuum degree of 3×10 -3 Pa, then introduce Ar with a flow rate of 180-220sccm, adjust the working pressure to be stable at 1.5-1.7Pa, set the pulse bias to -780~-800V, the bias duty cycle to 85-87%, and glow clean for 15-18min.
8. The method for preparing a Zr-BC coating having both high hardness and high toughness according to claim 6, characterized in that: In step (2), the ion bombardment cleaning process is as follows: after glow discharge cleaning, the Ar flow rate is adjusted to 180-200sccm, the working pressure is adjusted to be stable at 0.8-0.9Pa, the Zr target is turned on (the Zr target is connected to a high-power pulsed magnetron sputtering power supply), the Zr target power is set to 1-1.3kW, the pulse bias is -760~-800V, the bias duty cycle is 85-87%, and the bombardment cleaning time is 8-10min.
9. The method for preparing a Zr-BC coating having both high hardness and high toughness according to claim 6, characterized in that: In step (3), the process of depositing the Zr transition layer is as follows: after glow discharge cleaning and ion bombardment cleaning, the Ar flow rate is adjusted to 80-100 sccm, the deposition pressure is adjusted to be stable at 0.7-0.8 Pa, the Zr target is turned on (the Zr target is connected to a high-power pulsed magnetron sputtering power supply), the Zr target power is set to 1.0-1.2 kW, the pulse bias is -140 to -150 V, the bias duty cycle is 48-50%, and the deposition time is 20-23 min.
10. The method for preparing a Zr-BC coating having both high hardness and high toughness according to claim 6, characterized in that: The purity of the Zr target and the ZrB2 target is 99.95%. When the Zr-BC coating is deposited, as the acetylene flow rate increases, the contents of B, O and Zr elements in the coating show a downward trend, and the C content gradually increases.
